Antibodies to β2-Glycoprotein I Associated with Antiphospholipid Syndrome Suppress the Inhibitory Activity of Tissue Factor Pathway Inhibitor - Salemink, Irene; Blezer, Ron; Willems, George M.; Galli, Monica; Bevers, Edouard; Lindhout, Theo (Thrombosis and Haemostasis, 2000)
Anionic phospholipid membranes have a dual role in blood coagulation: they are essential for the initiation and propagation as well as for the limitation and termination of the blood coagulation process. Patients with the anti-phospholipid syndrome (APS) carrying antibodies against complexes of anionic phospholipids and plasma proteins, show in vitro inhibited phospholipid dependent coagulation reactions, whereas in vivo the presence of these antibodies is associated with an increased risk of thrombosis. In this study we focussed on the effects of these anti-phospholipid antibodies on the regulation of TF-mediated factor Xa (FXa) generation in plasma. We hypothesized that anti-phospholipid antibodies interfere with the phospholipiddependent inhibition by tissue factor pathway inhibitor (TFPI) of TFinduced coagulation. Indeed, total-IgG, anti-cardiolipin-IgG (aCL) and anti-β2GPI-IgG, isolated from patient plasmas, all stimulated TF-induced FXa generation in normal plasma. This enhanced FXa generation was not observed when the patient’s IgG was depleted of anti-β2GPI-IgG or when normal plasma was depleted of β2GPI or TFPI. Taken together, these data indicate that antibodies to β2GPI, circulating in patients with APS, suppress TFPI-dependent inhibition of TF-induced coagulation, which results in an increased FXa generation.
Keywords: Tissue factor; TFPI; FXa generation; anti-β2-glycoprotein I